Good News or Bad News, Which Do You Want First? The Importance of the Sequence and Organization of Information for Financial Decision-Making: A Neuro-Electrical Imaging Study - Yang, Wenting; Ma, Jianhong; Chen, Hezhi; Maglione, Anton G.; Modica, Enrica; Rossi, Dario; Cartocci, Giulia; Bonaiuto, Marino; Babiloni, Fabio (Frontiers in Human Neuroscience, 2018)
Abstract Investment decisions are largely based on the information investors received from the target firm. Thaler(1985) introduced the hedonic editing framework, in which suggests that integration/segregation of information influence individual’s perceived value. Meanwhile, when evaluating the evidence and information in a sequence, order effect and biases have been found in various areas. In this research, we consider both the variable of Organization of Information, either segregate or integrate, and the Order of the information, either in the order of Negative-Positive or in the order of Positive-Negative. Three groups of information are tested in the experiment: a piece of Big Positive information and a piece of Small Negative information (BP/SN); a piece of Big Negative information and a piece of Small Positive (BN/SP); and a piece of Small Positive information and a piece of Small Negative information (SP/SN). Apart from the behavioral result (investment decision), the study applied the gathering of the electroencephalographic rhythms variations, as well as the heart rate and galvanic skin response. The neurometric indicators here employed were the Approach-Withdrawal (AW) and the Emotional (EI) indexes. In all three groups of information, the behavioral results confirms the recency effect. In SP/SN, which represents the ordinary situation without any involvement of large scale information, results show no statistical significance in the Emotional Index. The Approach-Withdrawal Index is consistent with the behavioral results and shows recency effect. However, when receiving information in large scale, either big positive or big negative, emotion plays a role during decision-making. In both case of BP/SN and BN/SP, emotion is effected by organization of information. In the condition of BP/SN, neurometrics AWI result suggests more approach potentials when two pieces of information presented integrated. While in the case of BN/SP, we observe the influence of both order and organization. Individual favours separation of information with the order of Negative-Positive, the recency effect. The results of the research could be useful and brings some insight for companies and orgainizations in the aspect of information communication, especially when large-scale information is involved.